Anchored hybrid enrichment provides new insights into the phylogeny and evolution of longhorned beetles (Cerambycidae). (18th August 2017) - HADDAD, STEPHANIE; SHIN, SEUNGGWAN; LEMMON, ALAN R.; LEMMON, EMILY MORIARTY; SVACHA, PETR; FARRELL, BRIAN; ŚLIPIŃSKI, ADAM; WINDSOR, DONALD; MCKENNA, DUANE D.
Abstract: Cerambycidae is a species‐rich family of mostly wood‐feeding (xylophagous) beetles containing nearly 35 000 known species. The higher‐level phylogeny of Cerambycidae has never been robustly reconstructed using molecular phylogenetic data or a comprehensive sample of higher taxa, and its internal relationships and evolutionary history remain the subjects of ongoing debate. We reconstructed the higher‐level phylogeny of Cerambycidae using phylogenomic data from 522 single copy nuclear genes, generated via anchored hybrid enrichment. Our taxon sample (31 Chrysomeloidea, four outgroup taxa: two Curculionoidea and two Cucujoidea) included exemplars of all families and 23 of 30 subfamilies of Chrysomeloidea (18 of 19 non‐chrysomelid Chrysomeloidea), with a focus on the large family Cerambycidae. Our results reveal a monophyletic Cerambycidae s.s. in all but one analysis, and a polyphyletic Cerambycidae s.l. When monophyletic, Cerambycidae s.s. was sister to the family Disteniidae. Relationships among the subfamilies of Cerambycidae s.s. were also recovered with strong statistical support except for Cerambycinae being made paraphyletic by Dorcasomus Audinet‐Serville (Dorcasominae) in the nucleotide (but not amino acid) trees. Most other chrysomeloid families represented by more than one terminal taxon – Chrysomelidae, Disteniidae, Vesperidae and Orsodacnidae – were monophyletic, but Megalopodidae was rendered paraphyletic by Cheloderus Gray (Oxypeltidae). Our study corroborates some relationships within Chrysomeloidea that were previously inferred from morphological data, while also reporting several novel relationships. The present work thus provides a robust framework for future, more deeply taxon‐sampled, phylogenetic and evolutionary studies of the families and subfamilies of Cerambycidae s.l. and other Chrysomeloidea. Abstract : This paper presents the first higher‐level molecular phylogeny for longhorned beetles which provides a robust framework for future phylogenetic and evolutionary studies of the families and subfamilies of Chrysomeloidea. Cerambycidae s.s., Disteniidae and Vesperidae were recovered as monophyletic. Cerambycidae s.l. was recovered as nonmonophyletic and Megalopodidae was rendered paraphyletic by Oxypeltidae.